TINJAUAN HUKUM ISLAM TERHADAP AKAD NIKAH MELALUI TELEPON (STUDI KASUS PADA KELURAHAN LAMOKATO, KEC. KOLAKA, KAB. KOLAKA) - Muh. Imran umar; Muhammad Yusuf Nasir; Akmir Akmir (Jurnal Syariah Hukum Islam, 2022)
Islamic law is a set of regulations based on Allah's revelation and the sunnah of the Prophet regarding the behavior of mukhallaf humans which are recognized and believed to be binding for all who are Muslims. Islamic law is universal. Law must develop according to the social needs of the community, as the rule in fiqh that "law changes with the changing times and changing times". In reality, Islamic law is not yet idealistic and seems unable to anticipate changing times and tends to be far from justice. For example, old Islamic law products state that marriage or consent granted must be carried out in one assembly. The reason or legal illat of one assembly is to maintain the continuity and confidence of the witnesses for the two parties who are carrying out the contract. Social development in Indonesian society, especially in the field of technology is currently growing rapidly. Marriage in the Islamic concept is an inner and outer bond between a man and a woman and with the consent of both and based on love and affection agree to live together as husband and wife in a household bond. From the results of the study, it was found that the marriage contract via telephone in the view of Islamic law must fulfill the law and the requirements for marriage in its validity, as long as there is no firmness from law enforcement agencies. Which opinion is enforced in the religious court, then during the process of the consent granted there is no doubt and fulfills the pillars and conditions. In its implementation, it fulfills the requirements and pillars of marriage and does not conflict with the compilation of Islamic law, so the marriage is valid. This is corroborated by the provisions of articles 27 to 29 of the compilation of Islamic law, among others, not lapse of time, then it is carried out by the guardian of the marriage concerned and said directly by the groom over the telephone.